2018
DOI: 10.1097/md.0000000000009562
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptosis and inhibits proliferation in infantile hemangioma endothelial cells via downregulation of MCL-1 and HIF-1α

Abstract: Background:Curcumin has been used as an alternative medicine for the treatment of infantile hemangiomas (IHs); however, the mechanism underlying the effectiveness of curcumin in IHs remains largely unclear.Methods:In this study, we isolated primary human hemangioma endothelial cells (HemECs) from fresh surgical specimens of 3 patients. We treated HemECs by curcumin and investigated the alterations in proliferative and apoptotic signaling pathways with cell counting kit-8, flow cytometry, western blotting, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…HiF1α is significantly upregulated in proliferating IH tissues compared with involuting iH tissues, and an in vitro study indicated that hypoxia upregulated HiF1α expression in hemangioma stem cells (26). curcumin-mediated HiF1α downregulation inhibits cell proliferation and induces infantile hemangioma endothelial cell apoptosis (18). The results of the present study suggested that HiF1α was highly expressed in iH tissues, and the expression levels of HiF1α in proliferating iH tissues were higher compared with involuting iH tissues.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…HiF1α is significantly upregulated in proliferating IH tissues compared with involuting iH tissues, and an in vitro study indicated that hypoxia upregulated HiF1α expression in hemangioma stem cells (26). curcumin-mediated HiF1α downregulation inhibits cell proliferation and induces infantile hemangioma endothelial cell apoptosis (18). The results of the present study suggested that HiF1α was highly expressed in iH tissues, and the expression levels of HiF1α in proliferating iH tissues were higher compared with involuting iH tissues.…”
Section: Discussionmentioning
confidence: 49%
“…Hypoxia-inducible factor 1α (HIF1α) is a crucial regulator during hypoxia-induced angiogenesis, but it is also involved in the growth of hemangiomas ( 16 , 17 ). Curcumin-mediated downregulation of HIF1α inhibits the proliferation of human hemangioma endothelial cells (HemECs) ( 18 ). Furthermore, by using starBase, NEAT1 was predicted as a ceRNA that regulates HIF1α by sponging miR-33a-5p ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that HIF-1α inhibition induces apoptosis in many cancer cell lines, including glioblastoma (42,43). Furthermore, previous studies have reported that downregulation of MCL-1 and HIF-1α is implicated in curcumin-mediated apoptosis in infantile hemangioma endothelial cells (44). AKT is also involved in cell survival (45,46); It is activated by phosphorylation (47) and, herein, it was shown that LG inhibited the expression of p-AKT ( Figure 4B).…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] More recent reports also suggest alternative modalities for the treatment of this disease, such as the use of curcumin, indicating that the effectiveness of curcumin in hemangioma may be associated with its potent antiproliferative and apoptotic activities in hemangioma endothelial cells. 15…”
Section: Discussionmentioning
confidence: 99%